Associations of psychotic-like experiences, related symptoms, and working memory with functioning. Issue 1 (2020) - Chun, Charlotte A.; Cooper, Shanna; Ellman, Lauren M.
Abstract: This study examined the association of spatial working memory and attenuated psychotic-like experiences and related symptoms with social and role functioning. Findings from this study suggest that symptom dimensions and working memory impairment were associated with diminished functioning across a variety of domains. Specifically, negative symptoms and working memory impairment were inversely associated with both social and role functioning, whereas positive and disorganized symptoms showed inverse associations with social functioning only. Symptom dimensions did not moderate cognitive and functional variables, although working memory and attenuated clinical symptoms had an additive effect on functioning. Post-hoc analyses examining symptom dimensions simultaneously showed negative symptoms to be the variable most strongly predictive of overall functioning. These findings suggest that even in a non-clinical sample, sub-threshold psychosis symptoms and cognition may influence people's social and role functioning.